Saw damage gettering for industrially relevant mc‐Si feedstock - Shaw, E; Hamer, P; Collett, K; Bourrett-Sicotte, G; Bonilla, R; Wilshaw, P (Wiley‐VCH Verlag, 2017)
The silicon photovoltaic industry is currently shifting towards lightly doped emitters. These have electrical properties that benefit solar cells, compared to the traditional heavily doped emitters. This move brings new challenges, as gettering efficiencies of impurities are lowered as the doping reduces. This is particularly problematic in multicrystalline silicon (mc‐Si) since cell performance is typically boosted by the effective gettering of such impurities. In prior work, we proposed the novel gettering technique, saw damage gettering (SDG), which improved effective carrier lifetime of standard performance mc‐Si red zone material. In this work, we expand the study of SDG to various types of industrially relevant mc‐Si: upgraded metallurgical grade (UMG), high performance bottom red zone (HPRZ), and diamond sawn high performance (DHP). The optimal condition for SDG is found to be an annealing temperature of 850 °C. With this condition it was demonstrated that the effective carrier lifetime can be increased in all silicon types upon SDG. The largest increase was observed for HPRZ material by a factor of 10, and the largest final effective lifetime post SDG was that of UMG, with τeff = 61.3 µs. SDG is a potentially viable gettering method to work in conjunction with lightly doped emitters in removing the impurities of mc‐silicon feedstock and thus, improving the efficiency of the cells made therefrom.